Mengkaji Naskah Drama “Sepasang Merpati Tua” Karya Bakdi Soemanto Menggunakan Pendekatan Struktural Serta Nilai Pendidikannya - Anggita, Via; Waridah, Ira; Mutiara, Lia; Putra, Adita Widara (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
Literary works are one of the communication media to narrow ideas or ideas to connoisseurs, one example is drama. In this case, the author examines the play entitled